2019
DOI: 10.1002/solr.201800332
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Cyano‐Containing A2 Segments in A2‐A1‐D‐A1‐A2 Type Non‐Fullerene Acceptors to Combine with a Benzotriazole‐Based p‐Type Polymer: “Same‐Acceptor‐Strategy” for High VOC Organic Solar Cells

Abstract: To achieve efficient organic solar cells (OSCs), the design of promising non‐fullerene small molecular acceptors (SMAs) is crucially important and the relationship between the chemical structure and optoelectronic properties needs to be further investigated. Herein, an A2‐A1‐D‐A1‐A2 molecular skeleton is adopted to study the effect of end‐capped A2 groups containing different numbers of cyano units, where D and A1 are fixed as indacenodithiophene (IDT) and benzotriazole (BTA) units, respectively. Utilizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…(1) low energy offset, similar energy alignments between donor and acceptor materials; (2) high EQE EL to obtain low E loss,non‐rad . For the emerging highly efficient NFAs, the strong electron withdrawing cyano (CN) groups were frequently used, which decreases the lowest unoccupied molecular orbital (LUMO) level and luminescence intensity greatly . Therefore, removing the CN groups when developing new NFAs may be favorable for decreasing the E loss in OSCs.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…(1) low energy offset, similar energy alignments between donor and acceptor materials; (2) high EQE EL to obtain low E loss,non‐rad . For the emerging highly efficient NFAs, the strong electron withdrawing cyano (CN) groups were frequently used, which decreases the lowest unoccupied molecular orbital (LUMO) level and luminescence intensity greatly . Therefore, removing the CN groups when developing new NFAs may be favorable for decreasing the E loss in OSCs.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The equation J SC ∝ P light s , where S is the slope of the log–log plot of J SC versus P light , can be used to determine whether bimolecular recombination occurs within the photoactive layer . Except for the PBDB-T-2F:NC 70 BA binary PSC (the S value is 0.935), the S values of the PBDB-T-2F:IT-4F binary PSC and optimized ternary PSC are close to 1 (the S values are 0.980 and 0.982, respectively), suggesting an effectively suppressed bimolecular recombination for the PBDB-T-2F:IT-4F binary PSC and a further suppressed bimolecular recombination for the optimized ternary PSC. , Figure c shows the V OC dependence on light intensity ( P light ). According to the equation and the n value of the three PSCs (where n and k are the slope of the plot of V OC versus P light and the Boltzmann constant, respectively; T is the temperature in K; and q is the elementary charge), the high n value for the PBDB-T-2F:NC 70 BA binary PSC (the n value is 1.47) is ascribed to the Shockley–Read–Hall (SRH) recombination and is not negligible within the PBDB-T-2F:NC 70 BA binary films.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Both OSCs fabricated from PE1 and PE2 exhibited a high V oc over 1.1 V and the PE1:BTA3 blend delivered a higher PCE of 8.43% than PE2:BTA3 (5.83%). However, when blended with another high-performance polymer donor J71 with trimethyl(thiophen-2-yl)silane sidechains, the PCE of derived BTA3-based OSCs can be further improved to 8.60% with a V oc as high as 1.2 V [40]. Besides, Xiao et al [46] also fabricated the P3HT: BTA3 based OSCs, and found that a continuous pathway for electron transport can be resulted for BTA3 to further strengthen the electron mobility when forming BHJ blend with P3HT, thereby affording an encouraging PCE of 5.64% with a V oc of 0.90 V and an FF of 65%, much higher than the control P3HT:IDT-4CN devices (PCE = 2.55%).…”
Section: Nfas With a Tricyclic Electron-rich Corementioning
confidence: 99%
“…Due to the more electron-deficient property, INCN-based NFAs generally exhibit narrower bandgaps than RDbased NFAs, thereby showing higher short-circuit currents (J sc ) beyond 20 mA cm −2 [35,36]. By contrast, RD-based NFAs often present high open-circuit voltages (V oc ) up to 1.2 V [37][38][39][40]. To date, the best PCE from RDbased NFAs has exceeded 12% based on a ternary-blend OSC [41].…”
Section: Introductionmentioning
confidence: 99%